Влияние глицерина на устойчивость эритроцитов человека к гипертоническому и механическому стрессу - Шпакова, Н.М.; Орлова, Н.В.; Ніпот, О.Є.; Шапкіна, О.О.; Сєміонова, К.А. (Вісник проблем біології і медицини – 2013. – Вип. 3, Т.2 (103) – С. 352-355, 2013)
В работе показано, что глицерин значительно снижает уровень гипертонического шока эритроцитов человека и в то же время не оказывает влияния на уровень гемолитического повреждения этих клеток и проницаемость их мембран для катионов калия в условиях механического стресса. Предполагается, что влияние глицерина на клетки при разных видах стресса определяется его способностью изменять физико-химические характеристики клетки, которые непосредственно определяют их чувствительность к действию стрессовых факторов. ---------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------In this research there was studied the glycerol effect on human erythrocyte sensitivity to hypertonic and mechanical stresses. Hypertonic stress of erythrocytes was performed by transferring an aliquot of erythrocyte suspension into 4. 0 M NaCl solution (0.04% hematocrit). The hemolysis level as function of time was determined by recording a change in optical density of erythrocyte suspension (720 nm wavelength). Mechanical stress was done by mixing cell suspension (20% hematocrit) with plastic balls on a magnetic stirrer (rotation rate was 1,200 rot/min) at 22°C. In different time intervals there was determined the release of hemoglobin and potassium ions out of cells. When using glycerol the cells were incubated with the substance, after that they were subjected to stress effect. The study of glycerol effect on hypertonic stress of human erythrocytes allowed establishing the fact that an increase in substance concentration up to 1.0 M resulted in a significant (about an order of magnitude) reduction of erythrocyte hemolysis level during their following transfer into 4.0 M NaCl-contained medium. The influence of incubation duration of cells (2-10 min) with 0. 3 and 1.0 M glycerol on their sensitivity to hypertonic stress was studied. When using glycerol in 0. 3 M concentration, a gradual reduction in hypertonic hemolysis level of erythrocytes within the whole studied time range was observed. In the case of using 1.0 M glycerol no time dependence of hypertonic hemolysis of erythrocytes on incubation duration of cells with the substance was revealed since the minimum level of hypertonic damage was seen after 2 min cell incubation with glycerol. When studying the glycerol effect on erythrocyte resistance to mechanical stress the cells after 10 min incubation with cryoprotectant were subjected to mechanical action within different times (1.0, 1.5 and 2.0 hours). With an increase in mechanical stress duration higher level of hemolytic cell damage is observed. A similar time dependence of cell damage is also seen in glycerol presence in 1-3 M concentration. Increased erythrocyte resistance to mechanical stress is noted only if using 3 M glycerol under maximum duration of mechanical stress (2 hours). Quite a complete yield of potassium ions out of cells 1 hour later is observed under mechanical stress of erythrocytes in glycerol presence, whereas a hemolytic damage of erythrocytes is characterized by a pronounced time dependence within the whole range (1-2 hours). In this way glycerol significantly reduces the haemolysis level of human erythrocytes under hypertonic stress and does not practically affect the level of haemolytic cell damage and permeability of their membranes for potassium cations under mechanical stress. Glycerol effect on cells under various stresses is assumed to be determined by its ability to change physical and chemical characteristics of a cell that directly determine their sensitivity to stress factors.
Glycerol Effect on Human Erythrocytes Resistance to Hypertonic and Mechanical Stresses
Шпакова НМ, Орлова НВ, Нипот ЕЕ, Шапкина ОА, Семионова ЕА. Влияние глицерина на устойчивость эритроцитов человека к гипертоническому и механическому стрессу. Вісник проблем біології і медицини. 2013; 3(2):352-5
Keywords: гипертонический шок; механический стресс; эритроциты; глицерин